Stress symptoms and psychological components as measured in Malaysian students teachers - Peters, Martha Moore; Mutter, Jay Dominic; Yong, Leonard M.S.
This study examines the relationships among two stress symptoms, anxiety and tiredness and three psychological components that have been identified as useful in combating stress effects, namely, belief of control, approaching change as a challenge and preparation for stressful situation. Six commonly reported teaching sources of stress were selected as a bases for determining how strongly each individual experienced the stress symptoms and psychological components.
Keywords: Stress (Psychology).; Student teachers -- Malaysia -- Job stress; Student teaching -- Malaysia -- Psychological aspects